A Semantic Analysis of Metaphor Found in Selected Lyrics of "The Script", "Katy Perry", and "Michael Bublé" - Maulana, Rifki, Dra. Malikatul Laila, M. Hum (2017)
Semantics is the study of meaning in language. It can be implemented to analyze the literary work or nonliterary work. To understand the meaning of lyric songs, the writer focuses on the metaphor expression in the song. This research analyzes about semantic analysis of metaphor found in selected lyrics of "The Script", "Katy Perry", and "Michael Bublé". It will be analyzed by theory of Crystal, Beckson and Ganz about metaphor classification. The purposes of this research are (1) Identifying the types of metaphor which are found in selected lyrics of "The Script", "Katy Perry", and "Michael Bublé", (2) Describing the elements which are being compared in such metaphors of selected lyrics from "The Script", "Katy Perry", and "Michael Bublé", and (3) Explaining the functional meaning of the metaphor in selected lyrics of "The Script", "Katy Perry", and "Michael Bublé", and to describe the implication in the use of metaphor in education. This research is analyzed by using descriptive qualitative method because the writer uses description based on the quality comprehensive in the analysis. In analyzing data, the writer uses the theory of metaphor classification by Crystal, Beckson & Ganz (1999) and the theory of tenor and vehicle from Richards and Leech (1969). Then the writer describes the functional meaning of metaphor and its implication to comprehend the whole meaning contextually. There are 30 selected lyrics from "The Script", "Katy Perry", and "Michael Bublé" as the data in this research. Based on metaphor classification by Crystal, Beckson & Ganz (1999) there are three types of metaphor, namely conceptual metaphor, mixed metaphor, and poetic metaphor. In this research, the writer found 194 data of conceptual metaphor, 60 data of mixed metaphor, and 5 data of poetic metaphor. Conceptual metaphor is the dominant metaphor which is used in the song lyrics while poetic metaphor is the least and mixed metaphor is just one fourth of the whole percentage of the findings. The writer then describes the functional meaning of metaphor is to make the ideas of the lyrics more meaningful while the implication of metaphor in education is to enrich students' creative idea in writing skills.